Прогнозирование неустойчивых режимов работы ГТД - Герасименко, Владимир Петрович; Дехгани, М.; Каемиан, С. (НТУ "ХПИ", 2011)
Fundamental problems of gasdynamic instability have been considered. The criteries of static and dynamic instability are received. The attention take into consideration acoustic impedance of gasdynamic instability.
Keywords: аварийная ситуация; помпаж; вращающийся срыв; антипомпажные системы